Analysis of Customary Forest Legal Arrangements Post Constitutional Court Decision No. 35/2012 - Jemarut, Wihelmus; B , Kornelia Webliana (IHSA Institute, 2025)
The objective of this article is to examine the legal framework governing customary forests in the wake of the Constitutional Court's Decision No. 35 of 2012. Does the legislation contravene any established legal principles? What are the consequences of this decision? The research method employed is normative, with a conceptual and legislative approach. The findings of the study demonstrate that the legal regulations pertaining to customary forests subsequent to Constitutional Court Decision No. 35 of 2012 are not in accordance with the established legal hierarchy structure. This has an impact on the legal certainty of regulations on customary forests. One of the problems caused by the above is that the regulations on Customary Law Communities rights in the three ministerial regulations continue to change and have the potential to deviate from the spirit of Constitutional Court Decision No. 35 of 2012. As a result, the authority and rights of MHA over Customary Forests could be more explicit and are likely to always change when there is a change of minister. The results of this study make two (two) recommendations. First, legal regulations on Customary Forests must be addressed when preparing and discussing the Customary Law Community Bill. Second, there must be an explanation or proper interpretation of MHA rights over Customary Forests as intended in Constitutional Court Decision No. 35 of 2012